Do upstream migrating, juvenile amphidromous shrimps, provide a marine subsidy to river ecosystems?. (20th February 2017) - Novak, Peter A.; Bayliss, Peter; Crook, David A.; Garcia, Erica A.; Pusey, Bradley J.; Douglas, Michael M.
Abstract: The upstream migration of juvenile amphidromous shrimps has been proposed as a source of marine or estuarine‐derived nutrients into fresh water. Little is known about the size and ecological importance of any such subsidy as there have been few observational or empirical studies on the topic. We investigated the upstream migration of the amphidromous shrimp, Macrobrachium spinipes (Palaemonidae) in the Daly River, of tropical northern Australia, to determine migration phenology, estimate migration biomass and determine whether migrating shrimps transport marine‐derived energy and nutrients upstream. Field observations over 2 years revealed that juvenile M. spinipes migrate upstream en masse during extended periods of declining discharge over a period of 4–6 weeks during the wet season (March–May). In addition, juvenile atyid shrimps from the genus Caridina were also observed migrating upstream during the same period. Fine‐scale sampling using fyke nets over 2 years (2013 and 2014) consistently found discharge to be the strongest predictor of M. spinipes and Caridina spp. biomass, while moon illumination and cloud cover were also important predictors. An estimated 10–20 million shrimps migrated upstream during each wet season, transporting c . 100 kg of carbon and c . 28 kg of nitrogen per year. Muscle sulphur stable isotopes (δ 34 S) and exoskeleton strontium isotope ratios ( 87 Sr/ 86 Sr) were used to establish if marine carbon was transported upstream by the juvenile M. spinipes . Isotope data from migratory M. spinipes were compared to the non‐migratory freshwater Macrobrachium bullatum . No evidence of a marine signature in body tissue or exoskeleton was found using either technique, suggesting very rapid turnover of body tissues This study provides key insights into the migration phenology of amphidromous shrimps and, importantly, suggests that migrating M. spinipes do not transport significant amounts of marine‐derived energy and nutrients across the marine/freshwater ecotone.